Versatility of Free Cutaneous Flaps for Upper Extremity Soft Tissue Reconstruction - Wang, Howard D.; Alonso-Escalante, Jose C.; Cho, Brian H.; DeJesus, Ramon A. (Journal of Hand and Microsurgery, 2017)
The goals of upper extremity soft tissue reconstruction should go well beyond providing coverage and restoring function. As the field of reconstructive microsurgery has evolved, free cutaneous flaps (FCFs) are gaining wider application. The advantages of FCF include minimizing donor-site morbidity by preserving the muscle and fascia, improving versatility of flap design, and superior aesthetic results. This review highlights the application of anterolateral thigh, superficial circumflex iliac artery, deep inferior epigastric perforator, superficial inferior epigastric artery, and flow-through flaps for reconstruction of upper extremity defects. These flaps share several qualities in common: well-concealed donor sites, preservation of major arteries responsible of providing inflow to distal extremity, and potential for a two-team approach (donor and recipient sites). While the choice of flaps should be decided based on individual patient and defect characteristics, FCF should be considered as excellent options to achieve the goals of upper extremity reconstruction.
Keywords: free cutaneous flaps; upper extremity reconstruction; anterolateral thigh flap; superficial circumflex iliac artery flap; deep inferior epigastric perforator flap; superficial inferior epigastric artery flap